(untitled) (OCEM Journal of Management, Technology & Social Sciences, 2025)
This study examines the interplay among service quality, customer satisfaction, and customer loyalty within Nepal’s commercial banking sector. Customer satisfaction is crucial as it reflects the association between customer expectations and perceived service quality, significantly influencing customer loyalty and the industry’s overall health. This study aims to comprehend banking behaviors, assess satisfaction levels concerning service quality, elucidate the connection between satisfaction and loyalty, and identify factors that shape loyalty and satisfaction in Nepalese commercial banks. Methodologically, this research applied a descriptive approach to explore these dynamics thoroughly. It also applied a causal comparative method to establish robust relationships among service quality, customer satisfaction, and loyalty. The data collection process involved distributing questionnaire to customers of commercial banks in Kathmandu, surrounding both physical branches and online platforms. The analysis of the data depends on the use of MS Excel and SPSS software to interpret findings effectively. Key findings disclose significant correlations between different service quality dimensions. They are tangibility, reliability, assurance, empathy, technology, responsiveness, and customer satisfaction, with assurance emerging as a particularly influential predictors. Regression analysis further highlights the positive impact of assurance, technology, empathy, and tangibility on satisfaction, contrasting with lesser effects from reliability and responsiveness. Regarding customer loyalty, this study highlights the significant influence of customer satisfaction alongside empathy, whereas factors like reliability, responsiveness, tangibility, and technology show minimal impact. Ultimately, enhancing service quality especially assurance and empathy is crucial for improving satisfaction and cultivating final customer loyalty within Nepal’s commercial banking sector, a vital issue of banking industries.